Candi Jawar dalam Analisis Ruang Publik sebagai Sumber Sejarah Lokal - Nurhidayati*, Waode Yeny; Agung Novariyanto, Rizki; Sunuyeko, Nurcholis (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
This research is a qualitativeresearch, using a historical and descriptive approach. In this study, researchers will dig up in-depth information regarding the Njawar Temple as a Public Space, as well as how the public's perception of the Njawar Temple as a public space is also a source of local history, of course. The results of this study can be concluded that why is Njawar Temple not as famous as other temples because of its location which tends to be far from the reach of the public, also difficult access to the location and sofar the Njawar Temple which has functioned as a public space is located far from the crowds, until now the Jawar Temple is still full with mystery because not many historical studies have been revealed in it. The function of Jawar Temple in the aspect of public space is as a historical source and as a tourist destination for cultural heritage in the past. Penelitian ini berupa penelitian Kualitatif, dengan menggunakan jenis pendekatan historis dan deskriptif. Dalam penelitian ini peneliti akan menggali informasi sedalam-dalamnya terkait Candi Jawar sebagai Ruang Publik,juga bagaimana pemanfaatan candi Jawar sebagai sumber sejarah lokal. Hasil Penelitian ini dapat disimpulkan bahwa Candi Jawar mengapa tidak se famous Candi lainya karena lokasi nya yang cenderung jauh dari jangkauan Hingga kini candi Jawar masih penuh dengan misteri lantaran belum banyak kajian sejarah yang terungkap didalamnya. Fungsi Candi Jawar dalam aspek ruang public adalah sebagi sumber sejarah dan sebagai destinasi wisata warisan budaya, dahulu dimasa Kerajaan Majapahit Candi Jawar digunakan sebagai tempat Pendidikan atau Mandala Kedewaguruan dan saat ini fungsi candi Jawar dalam aspek ruang public adalah sebagai objek kajian sejarah dan sebagai tempat peribadatan.